2017
DOI: 10.1021/acs.organomet.7b00376
|View full text |Cite
|
Sign up to set email alerts
|

DFT Studies of Ru-Catalyzed C–O versus C–H Bond Functionalization of Aryl Ethers with Organoboronates

Abstract: Density functional theory calculations have been performed to investigate how different nucleophiles and directing groups affect the preference of C−H versus C−O bond functionalization in the ruthenium-catalyzed coupling reactions of aryl ethers with organoboronates. Our results indicate that the preference depends on the relative stability of the transition state structures for the C−O bond activation in the C−O bond functionalization pathway and the transmetalation with boronate to form a Ru−C bond in the C−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…4.4) program suite for DFT calculations. The PBE method was chosen as it has been previously used to study a number of metal-mediated reactions; in particular, a recent benchmarking study of iridium-mediated reactions found that PBE together with Grimme’s DFT-D2 empirical dispersion corrections outperformed a number of other methods. Geometry optimizations and vibrational frequency calculations were carried out using the effective core potentials (ECPs) of Hay and Wadt with the double-ζ valence basis set LANL2DZ for Rh and the 6-31G­(d) basis set for all other elements.…”
Section: Methodsmentioning
confidence: 99%
“…4.4) program suite for DFT calculations. The PBE method was chosen as it has been previously used to study a number of metal-mediated reactions; in particular, a recent benchmarking study of iridium-mediated reactions found that PBE together with Grimme’s DFT-D2 empirical dispersion corrections outperformed a number of other methods. Geometry optimizations and vibrational frequency calculations were carried out using the effective core potentials (ECPs) of Hay and Wadt with the double-ζ valence basis set LANL2DZ for Rh and the 6-31G­(d) basis set for all other elements.…”
Section: Methodsmentioning
confidence: 99%
“…Such differences lead us to the hypothesis of absence of agnostic activation in the oxidative addition step of C-H bonds in fluorenones. 34 On the other hand, the distance Ru•••O(-C) is also significantly smaller in 1bb (ca. 2.75-2.90 Å) than in 13b (ca.…”
Section: Cluster Syn Lettmentioning
confidence: 95%
“…In order to rationalize the lack of reactivity of the ortho-C-H bond of fluorenone (1a) and its 1-methoxy derivative 1b, we performed calculations at the DFT level (see Supporting Information for details) of the square-planar Ru(0) complexes of these compounds and those derived from 2methoxyacetophenone (13) for comparison (Figure 2). In addition, for comparison purposes, geometric data resulting from calculations reported for 13 by Lin and coworkers 34 at a different level of theory (PBE/LanL2DZ, plus f-type and d-type polarization functions for Ru and P, and 6-31G* for H, C and O) are also shown in Figure 2. Our results show a significant difference in Ru•••H distance and C-H elongation in fluorenone complexes (1aa, 1ba) when compared with that of acetophenone (13a).…”
Section: Cluster Syn Lettmentioning
confidence: 99%
“… 23 This reaction has been calculated to occur by oxidative addition of the C–O bond to a 16-electron ruthenium(0) complex, [Ru(PPh 3 ) 2 (CO)(L)] (L = substrate coordinated through the directing group). 24 In related studies, Bergman and co-workers have reported ruthenium catalysts for the hydrogen-shuttling sp 3 C–O bond cleavage of 2-aryloxy-1-arylethanols, simple models of the β-[O]-4′ linkage of lignin. Computational data again support the involvement of a Ru(0)/Ru(II) redox couple, and the key C–O bond breaking step is proposed to occur by oxidative addition to Ru(0).…”
Section: Introductionmentioning
confidence: 99%
“…23 This reaction has been calculated to occur by oxidative addition of the C−O bond to a 16-electron ruthenium(0) complex, [Ru(PPh 3 ) 2 (CO)(L)] (L = substrate coordinated through the directing group). 24 In related studies, Bergman and co-workers have reported ruthenium catalysts for the hydrogen-shuttling sp 3 and the key C−O bond breaking step is proposed to occur by oxidative addition to Ru(0). 25−27 Here we show that [Ru(H) 2 (N 2 ) 2 (PCy 3 ) 2 ] (1), originally reported as a reactive intermediate prone to decomposition, 28 can be isolated and effects both sp 2 C−H and sp 2 C−O bond activation of methyl aryl and biaryl ethers under exceptionally mild conditions (25−40 °C) provided the substrate contains a suitable ketone directing group adjacent to the C−X bond (X = H and OR).…”
Section: ■ Introductionmentioning
confidence: 99%